2020
DOI: 10.1123/jsr.2018-0179
|View full text |Cite
|
Sign up to set email alerts
|

Preseason Functional Performance Test Measures Are Associated With Injury in Female College Volleyball Players

Abstract: Context: Preseason functional performance test measures have been associated with noncontact time-loss injury in some athletic populations. However, findings have been equivocal with many studies consisting of heterogeneous populations. Objective: To determine if preseason standing long jump and/or single-leg hop test scores are associated with a noncontact time-loss injury to the lower quadrant (LQ = low back or lower-extremities) in female Division III college volleyball (VB) players. Design: Prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…The cutoff score for the limb asymmetry during the SLH was greater than 10% (at risk)/≤10% (reference). Risk profiles based on suboptimal performance on a battery of functional performance tests were also analyzed [9,10]. The first risk profile based on a battery of tests was dichotomized by the following: athletes who had an SLJ 79% of one's height or less and each SLH 69% of one's height or less [at risk]/all other athletes [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cutoff score for the limb asymmetry during the SLH was greater than 10% (at risk)/≤10% (reference). Risk profiles based on suboptimal performance on a battery of functional performance tests were also analyzed [9,10]. The first risk profile based on a battery of tests was dichotomized by the following: athletes who had an SLJ 79% of one's height or less and each SLH 69% of one's height or less [at risk]/all other athletes [10].…”
Section: Resultsmentioning
confidence: 99%
“…NCAA Division III female collegiate athletes (a heterogeneous sample including soccer players) were nine times more likely to experience a noncontact time-loss thigh or knee injury if one started the season with an SLJ <80% of one's height, bilateral SLH measures <65% of one's height, and a lower extremity functional test (an agility drill) of 118 seconds or more [9]. A homogeneous sample of female collegiate volleyball players who had lower SLJ (<80% height) and SLH (<70% height and a >10% side-to-side asymmetry) scores were four times more likely to experience a time-loss injury to the low back or lower extremity during the season [10]. Lower preseason SLJ and SLH scores have served as a marker for injury in heterogeneous populations and volleyball athletes; however, it is unknown if these tests can discriminate injury occurrence in a homogeneous population of female collegiate soccer athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Lai et al [29] determined that cutoff scores of 2, 3, and 9 cm for asymmetry in anterior, posterolateral, and posteromedial reach, respectively, along with the 4 cm cutoff point used in most prior studies, had poor sensitivity and specificity in regards to earlier or increased rates of injury in a sample of 294 NCAA Division I athletes. Most recently, Brumitt et al [30,31] found no associations between preseason YBT-LQ test scores and non-contact LQ injury in male collegiate basketball players or female collegiate volleyball players. Based on our present study's findings and recent reports, we suggest that the YBT-LQ test ability as a sole indicator for injury is limited in collegiate American Football players, and that other screening tests should also be assessed.…”
Section: Discussionmentioning
confidence: 98%
“…Studies investigating YBT-LQ performance have typically included three trials in each direction on each leg [11,15,24,[28][29][30][31]. Some studies have used the maximal reach distance of the trials [11,24,28,29], while others used the mean reach distance of the trials [15,30,31]. We chose to use the maximum of the three reach distance tests for our calculations for comparative purposes to Butler et al [11].…”
Section: Discussionmentioning
confidence: 99%